THE IMPACT OF PESTICIDE USE ON RESIDUALS IN VEGETABLE PRODUCTS IN PALANGKA RAYA - Normila; Maulia, RESNA; Ramadhani, Juni; Mansyah, Barto (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
ABSTRACT   Pesticide use in agriculture is essential for controlling pests and diseases; however, overuse often results in environmental contamination and health issues. This study explores the presence of pesticide residues in vegetables from Palangka Raya. The overuse of pesticides—whether in type, amount, frequency, or dosage—contaminates crops and poses risks to humans through inhalation and ingestion. Analytical observational research was conducted, using purposive sampling to collect vegetable samples. These samples were analyzed qualitatively with a pesticide detection kit, and the results were correlated with pesticide use on the farms. Data analysis was performed using McNemar's non-parametric test. The results revealed that 20% of the vegetable samples contained pesticide residues. These residues were significantly associated with a spraying frequency of more than twice per week (p = 0.016) and improper pesticide dosage (p = 0.039). This study underscores the impact of pesticide application practices on residue levels in vegetables, emphasizing the need for regulated use to minimize health risks.  Keywords: Residue; Pesticide; Vegetables; Agriculture;